RELATIONSHIP TO LEARN IN SCHOOL AND AT HOME WITH THE SUBJECT OF LEARNING STUDENT DEPARTMENT CURLINGHAIRSTYLING SMKN 3 PAYAKUMBUH - NURHASANAH, AYU; Hayatunnufus, Hayatunnufus; Rahmiati, Rahmiati (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2014)
SMK 3 Payakumbuh, still has some problems in teaching and learning. Judging from the way student learning is not good, indifferent and not serious in learning, then the views of the student learning outcomes, especially Subject Beauty Hair System curling on the subject found that student scores are still low.Research aims. 1) To see the relationship between learning the school with the results study.2) To see the relationship between learning at home with learning outcomes. 3) To see how much the relationship between learning at school and at home with learning outcomes in subjects curling hairstyling students major in SMKN 3Payakumbuh.This research is a descriptive study descriptive correlational method on subjects curling hairstyling courses in SMKN 3 Payakumbuh 2012/2013-2011/2012 school year as many as 40 people, all of whom serve as the study population. Data processing is done by determining the percentage of respondents based indicators and categorization of the studied and used for product moment correlation and hypothesis testing using test t.The results showed that 59 % of respondents have a way of learning in schools with unfavorable category, 64 % of respondents have a way of learning at home with unfavorable category , out of 40 students there are 28 students ( 70 % ) still have the learning outcomes in subjects curling hair < 70 with unresolved categor, and there were 12 students ( 30 % ) who have learning outcomes curling subjects â‰¥ 70 with complete categories. The results of the correlation analysis of the first hypothesis ( X1 - y ) is obtained by interpretation r count of 0.687 strong relationships with sig 0.000 < 0.05 . The second hypothesis ( X2 - Y ) obtained r count of 0,482 with the interpretation of the relationship, the value sig0, 002 < 0.05. The third hypothesis ( X1 , X2 - Y ) obtained R value ( 0.705 ), this shows that the relationship between learning at school and at home with the interpretation of learning outcomes with a strong relationship. Testing hypotheses to find the relationship to duavariabel free to Y of F obtained by ( 18.291 ) this value > F ( 2,252 ) and received the 95% confidence level . Â Keywords : How to learn, at school, at home, learning outcomes